2020
DOI: 10.1532/hsf.2899
|View full text |Cite
|
Sign up to set email alerts
|

New Treatment for Driveline Infection Following Implantation of a Ventricular Assist Device

Abstract: In patients with an implantable ventricular assist device (VAD), driveline infection (DLI) is a challenging complication. Once DLI occurs, it may lead to pump contamination and/or septicemia, which means that early treatment is essential. We hereby report our initial experiences of a mechanically-powered portable negative pressure wound therapy system (Smart Negative Pressure: SNaPTM) to treat DLI at an outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They have also used this ointment for disinfection immediately after implantation to prevent DLI in 6 patients with an extracorporeal left VAD (duration 4-240 days) and in 1 patient with the HMII, and none of these patients experienced infection. 115 It has been reported that allogeneic platelet gel (PLT-gel) 118 and platelet-rich plasma (PRP) 119 were effective in the treatment of DLIs. PLT-gels and PRP contain high a concentration of platelet-derived growth factors, transforming growth factor-β1, and vascular endothelial growth factor which enhances activity of fibroblasts, mesenchymal cells, and stromal cells in the process of wound healing.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…They have also used this ointment for disinfection immediately after implantation to prevent DLI in 6 patients with an extracorporeal left VAD (duration 4-240 days) and in 1 patient with the HMII, and none of these patients experienced infection. 115 It has been reported that allogeneic platelet gel (PLT-gel) 118 and platelet-rich plasma (PRP) 119 were effective in the treatment of DLIs. PLT-gels and PRP contain high a concentration of platelet-derived growth factors, transforming growth factor-β1, and vascular endothelial growth factor which enhances activity of fibroblasts, mesenchymal cells, and stromal cells in the process of wound healing.…”
Section: Treatmentmentioning
confidence: 99%
“…They have also used this ointment for disinfection immediately after implantation to prevent DLI in 6 patients with an extracorporeal left VAD (duration 4–240 days) and in 1 patient with the HMII, and none of these patients experienced infection. 115…”
Section: Management Of Dli—diagnostic Workup and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Equally critical is the practice of meticulous wound care protocols that are well adjusted to the needs of the different stages of DLIs. The progression of DLIs and the characteristics of percutaneous wounds are strong determinants of the selected therapeutic protocol, that can involve wound dressing in combination with supplementary treatments, such as negative pressure vacuum-assisted closure therapy, cold atmospheric plasma, and antibiotic beads (Bernhardt et al 2020 ; Haddad et al 2020 ; Hilker et al 2017 ; Kilo et al 2020 ; Sezai et al 2020 ). In many cases however, the therapeutic benefits are decapacitated by relapsing infections related to biofilm persistence.…”
Section: Clinical Protocols Against Driveline Infections (Dlis)mentioning
confidence: 99%